2018
DOI: 10.1177/0961203318758504
|View full text |Cite
|
Sign up to set email alerts
|

Increased visceral adipose tissue and altered adiposity distribution in premenopausal lupus patients: correlation with cardiovascular risk factors

Abstract: Objective Visceral adipose tissue (VAT) correlates with cardiovascular risk factors and has never been assessed in systemic lupus erythematosus (SLE). Our aim was to evaluate VAT in premenopausal SLE patients. Methods Sixty-three premenopausal SLE patients and 186 age-matched healthy women were included. Demographic, anthropometric, disease and treatment parameters were evaluated. VAT was measured by dual X-ray absorptiometry (DXA) with APEX 4.0 software. Results SLE patients had a disease duration of 5.25 ± 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
2
11
0
1
Order By: Relevance
“…In addition, LPC Seguro et al [9] failed to find that VAT was related to disease duration, SLEDAI score, SLICC/ACR-DI, or current glucocorticoid use. In the present study, we identified several SLE disease-related factors positively associated with increased VAT: SLE disease duration and SLICC/ ACR-DI score, whereas low complement C3/C4 was negatively associated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, LPC Seguro et al [9] failed to find that VAT was related to disease duration, SLEDAI score, SLICC/ACR-DI, or current glucocorticoid use. In the present study, we identified several SLE disease-related factors positively associated with increased VAT: SLE disease duration and SLICC/ ACR-DI score, whereas low complement C3/C4 was negatively associated.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the volume of PVAT was greater in female SLE patients than in age-and race-matched controls and associated with calcification in different vascular beds, which could influence CVD. LPC Seguro et al [9] used DXA to evaluate VAT in premenopausal patients with SLE, and they found that SLE was associated with increased VAT, and the latter was correlated with traditional CV risks. Our result was partly consistent with their result that premenopausal SLE patients with BMI less than 25 had a higher VAT parameter than controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seguro и соавт. [14] сравнили СТ у женщин с СКВ молодого возраста (31 год) и сопоставимых по возрасту, массе тела и ИМТ здоровых доно-С О В P E М Е Н Н А Я Р Е В М А Т О Л О Г И Я № 1 ' 2 0 О Р И Г И Н А Л Ь Н Ы Е И С С Л Е Д О В А Н И Я / O R I G I N A L I N V E S T I G A T I O N S ров. Пациентки не отличались по количеству общего жира, но имели больше висцерального жира (по массе, объему и площади; p=0,001).…”
Section: Conclusion Most Women With Sle Have Ao Increased Adipose Tunclassified